2003
DOI: 10.4161/cbt.2.5.441
|View full text |Cite
|
Sign up to set email alerts
|

Altered HOX Gene Expression in Human Skin and Breast Cancer Cells

Abstract: Human HOX genes are expressed in a spatio-temporal fashion during embryogenesis and early development where they act as master transcriptional regulators. HOX genes are also expressed in normal adult cells, potentially in a tissue specific manner involving maintenance of the normal phenotype. In selected oncogenic transformations, mis-expression of many HOX genes have been shown, indicating an involvement of these transcriptional regulators in carcinogenesis and metastasis. Utilising quantitative real-time RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…In addition, both mRNA levels and protein levels of HOXA1 are significantly correlated with chemotherapy response in human patients. HOXC13 has also been shown to be strongly and progressively expressed in human melanoma and highly expressed in cells of the MCF-7 breast cancer cell line (119,120). Our findings that Hoxa1 and Hoxc13 are direct downstream targets of YAP in the epithelial tissues of developing tooth and the epidermis of skin may provide insights into understanding the molecular mechanisms of YAP in not only organism development but also human disease onset and progression.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, both mRNA levels and protein levels of HOXA1 are significantly correlated with chemotherapy response in human patients. HOXC13 has also been shown to be strongly and progressively expressed in human melanoma and highly expressed in cells of the MCF-7 breast cancer cell line (119,120). Our findings that Hoxa1 and Hoxc13 are direct downstream targets of YAP in the epithelial tissues of developing tooth and the epidermis of skin may provide insights into understanding the molecular mechanisms of YAP in not only organism development but also human disease onset and progression.…”
Section: Discussionmentioning
confidence: 85%
“…A putative role of HOXs in malignant processes has been well documented in leukemia (35)(36)(37). Several HOXs also have been implicated in solid tumors, such as breast, colonic, rectal, gastric, lung, renal, colorectal, cervical and testicular carcinomas (11,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). It seems that whereas some HOXs have the same expression in normal and malignant tissues, others exhibit altered expression in cancer lesions, suggesting an association with cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, 39 HOXs have been identified that are spread in four different clusters located on four separate chromosomes: 7 (HOXA), 17 (HOXB), 12 (HOXC) and 2 (HOXD) (18). Some HOXs, including HOXA10, have been implicated in several solid tumor types (11,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 14/25 genes exhibited differential expression levels in malignant breast tissues compared with non-malignant breast tissues (51). Several studies have demonstrated that various HOX genes are differentially expressed (either up-or downregulated) in patients with breast cancer, indicating the involvement of these genes in carcinogenesis and breast cancer metastasis (43,52,53). In addition, HOXA5 and HOXA9 have been implicated as regulators of p53 and breast cancer 1 (BRCA1), respectively, which are important factors in cancer development (54,55).…”
Section: Hox Genes and Cancermentioning
confidence: 99%